2020
DOI: 10.1038/s41598-020-75812-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cytokine expression and circulating immune cell subsets as potential parameters of acute radiation toxicity in prostate cancer patients

Abstract: One of the challenges of radiation oncology in the era of personalized medicine is identification of biomarkers associated with individual radiosensitivity. The aim of research was to evaluate the possible clinical value of the associations between clinical, physical, and biological factors, and risk for development of acute radiotoxicity in patients with prostate cancer. The study involved forty four patients treated with three-dimensional conformal radiotherapy. The concentrations of IL-1β, IL-2, IL-6, IFN-γ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 33 publications
2
25
0
1
Order By: Relevance
“…MicroRNA-34a also changes the expression profile of cytokines such as interleukin 6 (IL-6), and tumor necrosis factor alpha (TNFα), thus regulating the inflammatory response 27 . Besides that, it has been noticed that IL-6 and transforming growth factor beta ( TGF-β ) gene expression levels change in PBMC in prostate cancer patients receiving RT 38 . MicroRNA-10b was shown to decrease radiation-induced apoptosis in glioblastoma cells 25 .…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA-34a also changes the expression profile of cytokines such as interleukin 6 (IL-6), and tumor necrosis factor alpha (TNFα), thus regulating the inflammatory response 27 . Besides that, it has been noticed that IL-6 and transforming growth factor beta ( TGF-β ) gene expression levels change in PBMC in prostate cancer patients receiving RT 38 . MicroRNA-10b was shown to decrease radiation-induced apoptosis in glioblastoma cells 25 .…”
Section: Discussionmentioning
confidence: 99%
“…IFN-γ and IL-6 increased significantly during IMRT, and the increased expression of IL-2 and IL-1 was related to acute gastrointestinal and genitourinary toxicity. In another study, circulating cytokine levels were assessed before RT, after 1, 3 and, 5 weeks, at RT completion, and 1 month after completion [ 24 ]. This study showed that IL-6 was significantly associated with the severity of acute genitourinary and gastrointestinal toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The radiation-induced inflammatory response and specific changes in the levels of circulating cytokines have been associated with the occurrence of side effects in cancer patients undergoing radiotherapy, such as normal tissue radiotoxicity and fatigue symptoms [ 24 26 ]. In our previous studies, we have shown associations between individual, clinical factors, biological parameters, and the risk for development of acute radiotoxicity in patients with prostate cancer treated with radiotherapy [ 12 , 27 ]. The increased serum levels of IL-6 during the course of radiotherapy in patients with prostate cancer had been reported to be significantly associated with higher grade of acute GU toxicity across radiotherapy [ 27 ].…”
Section: Introductionmentioning
confidence: 99%